Determining pore size distribution in wet earlywood cell wall by solute exclusion using total organic carbon technique (TOC) - Rolleri, Aldo; Burgos, Francisco; Bravo-Linares, Claudio; Vásquez, Ester; Droppelmann, Fernando (Wood science and technology, 2014)
Solute exclusion is a probe technique useful to determine the pore volume and pore size distribution of a cell wall network; however, accurate measuring of molecular probe concentration is critical. In this study, the concentration of polyethylene glycol (PEG) and glucose was measured by detection of their organic carbon using a total organic carbon (TOC) equipment. PEG and glucose concentration by TOC is based on the quantitative oxidation of the organic matter contained in the solution, and then, produced CO₂ is stoichiometrically correlated with the TOC value. In this work on Pinus radiata earlywood cell wall, the fiber saturation point was 0.72 mL/g and it was reached by a molecular probe size with a radius of gyration R g = 5.96 . Moreover, the mean pore size present in the wood samples has a size equivalent to a molecular probe with a radius of gyration of 3.77 . Since TOC is based on the quantitative oxidation of the organic matter contained in the solution, it is essential to wash and rinse the wood samples to prevent that other carbon sources as extractives modify PEG and glucose concentration. Finally, the accuracy of TOC to determine the pore size distribution in the wet wood cell wall is subject to limitations of the solute exclusion technique.